2020
DOI: 10.1111/his.14120
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tissue‐based molecular biomarkers: a practical categorisation based on the 2019 World Health Organization classification of epithelial digestive tumours

Abstract: Molecular biomarkers have come to constitute one of the cornerstones of oncological pathology. The method of classification not only directly affects the manner in which patients are diagnosed and treated, but also guides the development of drugs and of artificial intelligence tools. The aim of this article is to organise and update gastrointestinal molecular biomarkers in order to produce an easy‐to‐use guide for routine diagnostics. For this purpose, we have extracted and reorganised the molecular informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…The first glimmer of hope for a paradigm shift in the colon cancer classification came recently with the latest (5 th ) edition of the WHO Digestive System Tumors, which introduced the immune response as essential and desirable diagnostic criteria for colorectal cancer, and cited the consensus Immunoscore assay as the evidence of the immune response prognostic power in colon cancer. 1 A meta-analysis of the prognostic value of Immunoscore on more than 10,000 patients also confirmed that the consensus Immunoscore provided a reliable estimate of the recurrence risk in colon cancer. 2…”
Section: Current Classification Of Colon Cancermentioning
confidence: 65%
“…The first glimmer of hope for a paradigm shift in the colon cancer classification came recently with the latest (5 th ) edition of the WHO Digestive System Tumors, which introduced the immune response as essential and desirable diagnostic criteria for colorectal cancer, and cited the consensus Immunoscore assay as the evidence of the immune response prognostic power in colon cancer. 1 A meta-analysis of the prognostic value of Immunoscore on more than 10,000 patients also confirmed that the consensus Immunoscore provided a reliable estimate of the recurrence risk in colon cancer. 2…”
Section: Current Classification Of Colon Cancermentioning
confidence: 65%
“…In this study, we developed a deep-learning based pipeline that successfully recognizes and separates original image cancer, a robust prognostic scoring system [12,15] evaluated on digital slides using a CAD tool [32] and recently introduced among the "Essential Criteria" in WHO classification of digestive system tumors [33]. Most of the remaining immune variables can be evaluated only with time-consuming, poorly-reproducible methods which make them unsuitable for practical purposes.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with colorectal cancer (CRC), considerable intra-stage variability in clinical outcome is observed that is not predicted by the Tumor-Node-Metastasis (TNM) staging system. 1 The impact of the preexisting intratumoral adaptive immunity on tumor progression and invasion and on the patient's clinical outcome has been demonstrated. 2 This led to a major paradigm shift in tumor immunology, and to the development of an immune-based scoring system named Immunoscore.…”
Section: Immune Response and Colon Cancer Classificationmentioning
confidence: 99%
“…The consensus Immunoscore assay was cited as evidence that the immune response can improve prognostication in colon cancer. 1 The N0147 results, together with the introduction into the WHO guidelines, highlight the benefit of implementing Immunoscore into clinical practice and strongly advocate for the introduction of a new TNM-Immune classification system. The consensus Immunoscore is a powerful prognosis marker and a predictive marker of response to chemotherapy for stage III colon cancer patients.…”
Section: Immunoscore For Patient Management Decisionsmentioning
confidence: 99%
See 1 more Smart Citation